VD_FINDINFO Décision / 2013 / 861 vom 27. Juli 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. c CPP (CH), 221 CPP (CH)